2018
DOI: 10.1136/jmedgenet-2018-105599
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in neurofibromatosis type 1 is a function of the type of NF1 gene mutation: a new genotype-phenotype correlation

Abstract: BackgroundNeurofibromatosis type 1 (NF1) predisposes to breast cancer (BC), but no genotype-phenotype correlations have been described.MethodsConstitutional NF1 mutations in 78 patients with NF1 with BC (NF1-BC) were compared with the NF1 Leiden Open Variation Database (n=3432).ResultsNo cases were observed with whole or partial gene deletions (HR 0.10; 95% CI 0.006 to 1.63; p=0.014, Fisher’s exact test). There were no gross relationships with mutation position. Forty-five (64.3%; HR 6.4–83) of the 70 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 54 publications
0
22
2
1
Order By: Relevance
“…In addition to these four genotype-phenotype correlations, the findings of recent studies suggest that the type and the position of NF1 mutations may be the main determinant of the risk of developing spinal neurofibromas (patients more likely to have MS or SS mutations) [57], pulmonary stenosis (a significantly higher prevalence of non-truncating NF1 mutations) [58], breast cancers (a higher proportion of both nonsense and missense mutations) [12], and OPGs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to these four genotype-phenotype correlations, the findings of recent studies suggest that the type and the position of NF1 mutations may be the main determinant of the risk of developing spinal neurofibromas (patients more likely to have MS or SS mutations) [57], pulmonary stenosis (a significantly higher prevalence of non-truncating NF1 mutations) [58], breast cancers (a higher proportion of both nonsense and missense mutations) [12], and OPGs.…”
Section: Discussionmentioning
confidence: 99%
“…The enormous number of reported pathogenic NF1 variations consist of intragenic NF1 mutations, which are found in about 90% of NF1 patients, and large 17q11.2 deletions encompassing the entire NF1 gene and a number of flanking genes (the NF1 microdeletion), which are found in 5%-10% [9]. Point mutations are observed in all exons and are mostly nulling or protein-truncating mutations, while a minority (9.4%-15%) are missense mutations [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This increases the possibility that mutation, deletion, or duplication of the NF1 gene may affect the BRCA1 gene. There is another possibility that types of NF1 mutations, including non-sense mutations and missense mutations determine the different breast cancer risk between individuals ( 21 ). Epidemiological studies have shown that the peak incidence of breast cancer in Asia and the West varies, ranging from between 40 and 50 years in Asia and 60 and 70 years in the West ( 22 - 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…The increased risk of breast cancer in NF1 has now been reported by numerous groups, including a recent review of the literature which examined 32 published epidemiological studies focused on the potential association of NF1 and increased breast cancer risk [9,10,11,12]. Interestingly, Frayling et al, provided evidence that breast cancer risk in NF1 patients may be limited to certain NF1 variants [23], suggesting that only a subset of women may require enhanced screening. Nevertheless, high-risk breast cancer screening is currently recommended for all women with NF1; however, there is a lack of data regarding the feasibility and effectiveness of this screening.…”
Section: Introductionmentioning
confidence: 99%